2022
DOI: 10.1126/sciadv.abl5032
|View full text |Cite
|
Sign up to set email alerts
|

Selective endocytosis of Ca 2+ -permeable AMPARs by the Alzheimer’s disease risk factor CALM bidirectionally controls synaptic plasticity

Abstract: AMPA-type glutamate receptors (AMPARs) mediate fast excitatory neurotransmission, and the plastic modulation of their surface levels determines synaptic strength. AMPARs of different subunit compositions fulfill distinct roles in synaptic long-term potentiation (LTP) and depression (LTD) to enable learning. Largely unknown endocytic mechanisms mediate the subunit-selective regulation of the surface levels of GluA1-homomeric Ca 2+ -permeable (CP) versus heteromeric Ca 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Further, our data indicated a possible increase of Ca 2+ -permeable GluA1 homomers (CP-AMPARs) by p85S6K. Elevated surface CP-AMPARs have been shown to facilitate LTP and improve hippocampus-dependent spatial learning [ 24 ]. The expression of GluA1 is down-regulated in the brains of AD patients and transgenic AD mice [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Further, our data indicated a possible increase of Ca 2+ -permeable GluA1 homomers (CP-AMPARs) by p85S6K. Elevated surface CP-AMPARs have been shown to facilitate LTP and improve hippocampus-dependent spatial learning [ 24 ]. The expression of GluA1 is down-regulated in the brains of AD patients and transgenic AD mice [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 98%
“…S13). Risk factors such as β-amyloid can affect the phosphorylation of GluA1 at Ser845 and surface level of GluA1, causing reduction of surface CP-AMPARs or abnormal synaptic CP-AMPAR incorporation [ 24 , 61 , 62 ]. Our study demonstrated that overexpression of p85S6K increased surface GluA1 via phosphorylation of GluA1 at Ser845 and improved learning and memory in AD mice, implicating that p85S6K may restore the CP-AMPARs in AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Peri-PSD CCSs play a specific role in post-synaptic receptor endocytosis, 25 even if some AMPARs may internalize through clathrin independent endocytosis. [28][29][30] How does imaging of CCSs reveal the dynamics of CME? The CCSs are transient structures appearing and disappearing in living cells: this would reflect the clustering of cargo, invagination to form a vesicle, scission, clathrin uncoating, and movement away from the plasma membrane.…”
Section: Imaging Of Individual Exocytosis Eventsmentioning
confidence: 99%
“…PICALM and related ANTH-domain-containing proteins modulate the surface levels of calcium-permeable AMPA-type glutamate receptors (AMPARs) that mediate fast excitatory neurotransmission and excitotoxicity [ 61 ]. PICALM is thereby supposed to play roles in synaptic plasticity and learning by modulating both long-term potentiation (LTP) and long-term depression (LTD) [ 62 ].…”
Section: Biology Of Picalmmentioning
confidence: 99%